👤

rezolvati ecuatia 2x pe 3 -2x+ 3 pe 12=x-2 pe 6- 1 pe 3-x+3 pe 4

Răspuns :


[tex] \frac{2x}{3} - \frac{2x + 3}{12} = \frac{x - 2}{6} - \frac{1}{3} - \frac{x + 3}{4} \\ \\ 8x - 2x - 3 = 2(x - 2) - 4 - 3(x + 3) \\ \\ 6x - 3 = 2x - 4 - 4 - 3x - 9 \\ \\ 6x - 3 = - x - 17 \\ \\ 6x - 3 + x = - 17 \\ \\ 7x - 3 = - 17 \\ \\ 7x = - 17 + 3 \\ \\ 7x = - 14 \\ \\ x = - \frac{14}{7} \\ \\ x = - 2 [/tex]

2x/3 - 2x+3/12 =x-2/6 - 1/3 - x+3/4=

Amplificam fractiile.(numitorul comun este 12)

8x/12 -2x+3/12 =2x-4/12 -4/12 - 3x+9/12

8x-(2x+3)/12 =2x-4-4-(3x+9)/12

8x-2x-3/12=2x-8-3x-9/12

6x-3/12= -x-17/12

Eliminam numitorul

6x-3= -x-17

6x+x= -17+3

7x= -14

x= -2